Engineering physiologically stiff and stratified human cartilage by fusing condensed mesenchymal stem cells - Bhumiratana, Sarindr (Methods, 2015)
For a long time, clinically sized and mechanically functional cartilage could be engineered from young animal chondrocytes, but not from adult human mesenchymal stem cells that are of primary clinical interest. The approaches developed for primary chondrocytes were not successful when used with human mesenchymal cells. The method discussed here was designed to employ a mechanism similar to pre-cartilaginous condensation and fusion of mesenchymal stem cells at a precisely defined time. The formation of cartilage was initiated by press-molding the mesenchymal bodies onto the surface of a bone substrate. By image-guided fabrication of the bone substrate and the molds, the osteochondral constructs were engineered in anatomically precise shapes and sizes. After 5 weeks of cultivation, the cartilage layer assumed physiologically stratified histomorphology, and contained lubricin at the surface, proteoglycans and type II collagen in the bulk phase, collagen type X at the interface with the bone substrate, and collagen type I within the bone phase. For the first time, the Young’s modulus and the friction coefficient of human cartilage engineered from mesenchymal stem cells reached physiological levels for adult human cartilage. We propose that this method can be effective for generating human osteochondral tissue constructs.